Energy balance of Sakha Republic snor thern administrative districtsand Chukchi Autonomous District - V. E. Zakharov; A. E. Ivanov (Известия высших учебных заведений: Проблемы энергетики, 2017)
Theworkformedtheactual energy balances of the northern administrative districts of the Republic of Sakha (Yakutia) and Chukchi Autonomous District in 2012. The perspective changes of energy balances these territories emphasized.